The Effect of Agnihotra Ash in Commercial Diet On Internal Organ of Broiler Chickens on The Age Of 5 Weeks - I W. A., Pratama; Siti, N. W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2018)
This study aims to determine the effect of Agnihotra ash in commercialdiet on internalorgan of broiler chickens on the age of 5 weeks.This research was conducted in the cage owned by Mr. I Ketut Sunatra located at Br. Anyar, Kediri, Tabanan,Bali. There were 80 day old chicks CP 707 (unsexed) used in the study. The animal were bought at PT. Tohpati Poultry Shop, Denpasar – Bali. The experimentaldesign used was Completely Randomized Design (CRD) consisted of 4 treatments and 4 replications.So, there were 16 units of the study.The treatments were: A : commercial diet without Agnihotra ash (control), B :commercial diet + 0.1% Agnihotra ash, C :commercial diet + 0.2% Agnihotra ash and D :commercial diet + 0.3% Agnihotra ash. The variables observed were : weight of heart, liver, spleen, bile, and gizzard. The results of study showed that Agnihotra ash on the level of 0.1%-0.3% in commercial diet tend to increase the weight of heart, liver, bile and gizzard, but statistically they were no significant difference (P>0.05). Based on the results of the study it can be concluded that Agnihotra ash at the level of 0.1%-0.3% in diet did not affect on internal organs (the weight of heart, liver, spleen, bile and gizzard) of broiler on the age of 5 weeks. Keywords: Broiler, internal organs, Agnihotra ash